The effects of pollen dispersal and mating pattern on inbreeding depression and hybrid vigor in Balfourodendron riedelianum (Engl.) Engl. (Rutaceae) - Aguiar, Bruna I.; Freitas, Miguel L. M.; Zannato, Antonio S.; Tambarussi, Evandro V.; Moraes, Mario L. T. [UNESP]; Ambrosano, Marcelo N.; Pereira, Lya C. S. M.; Gandara, Flavio B.; Kageyama, Paulo Y.; Sebbenn, Alexandre M. (Springer, 2020)
Worldwide, the significant fragmentation of tropical forests has resulted in the isolation of tree populations; this in turn has affected genetic diversity due to increases in inbreeding, leading to inbreeding depression (ID). Ex situ provenance and progeny trials are an effective strategy for population genetic conservation that can help combat the negative impacts of forest fragmentation on tree populations. Balfourodendron riedelianum is an endangered tree of the Atlantic Forest, for which conservation and environmental reforestation strategies are needed to ensure the preservation of the species. Microsatellite loci were used to genotype adult trees and descendant seedlings in an ex situ provenance and progeny trial located in Sao Paulo State, Brazil. The aim was to inform seed production management strategies for environmental restoration based on estimates of effective population size (N-e), pollen dispersal, mating pattern and ID for the traits root collar circumference (RCC) and plant height (H). The N-e (148.9) is adequate for sort-term ex situ conservation. Seedlings were predominantly outcrossed (93-96.2%), but selfing (3.8-7%) and mating between relatives (20-28.1%) show that the species is self-compatible. Pollen was dispersed through a pattern of isolation by distance. Selfed and biparental inbred seedlings showed lower values of RCC (2.98-3.10 mm) and observed heterozygosity (H-o = 0.25-0.34), and higher fixation index (F = 0.29-0.61) than seedlings from mating between unrelated trees (RCC = 3.30 mm, H-o = 0.51, F = 0.07). Mating among full-sibs showed the highest ID (8.1-12.4%). In the studied provenance and progeny trial, the selection of one tree per plot can minimize the production of biparental inbred seeds. Our results show that the provenance and progeny trial can serve as a seed source for environmental restoration.
Keywords: Genetic conservation; Inbreeding depression; Mating system; Microsatellite markers; Quantitative traits; Tropical tree